Entrepreneurship's requisite areas of development: A survey of top executives in successful entrepreneurial firms - Hood, Jacqueline N.; Young, John E. (Journal of Business Venturing, 1993)
Precisely what does one “need to know” in order to become a successful entrepreneur? When should we first begin teaching this knowledge? How should this knowledge be conveyed? These questions and others were answered by 100 leading entrepreneurs and chief executive officers in America's fastest-growing entrepreneurial firms. Questions such as those listed above are rapidly taking on increased importance not only for enhancing U.S. national competitiveness, but also around the world. For instance, eastern block countries wish to understand these questions as they attempt to establish free market economies and foster the entrepreneurial spirit, while developing countries need answers as they turn more toward entrepreneurship as a viable vehicle for promoting economic development and improved living standards for their citizens. This research develops a theoretical framework suggesting four primary areas in which successful entrepreneurs must be developed. Specifically, these areas are content, skills and behavior, mentality, and personality. The first three areas, content, skills and behavior, and mentality are referred to as areas of creative knowledge. This is because new knowledge is brought into existence during the creation and subsequent management of growing business entities. The study analyzes the responses of 100 chief executives from Inc. magazine's list of the nation's most successful publicly held entrepreneurial firms for the years 1979–1989. A list of requisite areas of knowledge in terms of content, skills, and mentality is developed. Personality characteristics necessary for entrepreneurial achievement are also delineated. Examples of essential domains of knowledge include finance/cash management, engineering, accounting, etc. in the area of content. Leadership, communication, and human relations are some of the skills and behaviors deemed essential. Creativity, opportunistic thinking, vision, and positive thinking are examples of required mentality attributes. Self-motivation, propensity for risk-taking, and deep-seated ethical values are required in terms of personality characteristics. After determining the areas of knowledge required for successful entrepreneurship, the study goes further to determine (1) if the executives believe the knowledge can in fact be taught, (2) the priority level of importance of the knowledge, and (3) suggested methods for conveying or teaching such knowledge. The results of the study represent a first attempt in the U.S. for systematically determining, from successful entrepreneurs, the knowledge believed important for engendering successful entrepreneurship. The results will help the designers of entrepreneurship education curricula in deciding which areas might be included in such curricula and which should receive greater emphasis. Finally, while the results could very well be different in other cultures and countries, they could represent a starting point for further analysis in other parts of the world as governments, academicians, and business communities attempt to foster the entrepreneurial spirit as a means of economic development and improvement of local standards of living.